A new species of the hippolytid genus Paralebbeus Bruce & Chace, 1986 (Crustacea: Decapoda: Caridea) from the Coral Seamount, southwestern Indian Ocean - Komai, Tomoyuki (Zootaxa, 2013)
The hippolytid genus Paralebbeus Bruce & Chace, 1986, is only known from two species, P. zotheculatus Bruce & Chace, 1986 (type species) and P. zygius Chace, 1997. Both are known from the western Pacific, though P. zotheculatus was orig-inally described from the Australian Northwest Shelf in the Indian Ocean. In this paper, a new species, P. mollis, is de-scribed and illustrated on the basis of a single ovigerous female from the Coral Seamount, southwestern Indian Ocean, at a depth of 952 m as the third representative of the genus. The new species is readily distinguished from its congeners by the rostrum being armed with one tooth on both the dorsal and ventral margin and the conspicuous pterygostomial tooth on the carapace. Because of these characteristics of the new species, the diagnosis of Paralebbeus is slightly emended. The holotype of P. mollis n. sp. was associated with an unidentified hexactinellid sponge, like the other two known spe-cies.